GaN-Based Generic Bifunction LED for Potential Duplex Free-Space VLCs - Lilin Liu; Xiangying Zhang; Zhenkun Sun; Bing Yan; Dongdong Teng; Gang Wang (IEEE Photonics Journal, 2017)
A generic bifunction GaN light-emitting diode (LED) structure, which has a 300 nm n+ -ZnO epitaxial layer grown on a standard GaN LED epistack and a mesa size of $200\, μ {\rm{m\, × \, 600\, }}μ {\rm{m}}$ , exhibits a peak responsivity of 450 mA/W to purple lights (380–400 nm) under zero bias and a narrow bandpass of around 60 nm. The corresponding product of quantum efficiency and gain is estimated as 140%. The purple light (380–400 nm) to blue light (>460 nm) rejection ratio can reach two orders of magnitude. The generic bifunction LED does not sacrifice its optical and modulation performances as a light transmitter. The optical power reaches 100 mW with a peak wavelength around 447 nm. A new proposition for duplex free-space visible light communications is depicted.